Analisis Tindakan Preventif Penggunaan Narkoba Pada Remaja Usia Produktif di Surabaya menggunakan PYD Logic Model Studi Kasus: Rumah RANJAU SMAN 21 Surabaya - Mulyaningsih, Sri; Pertiwi, Citra (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
In third world countries, controlling the use and consumption of alcohol, tobacco, and types of drugs that can influence other awareness becomes an important national issue. In the first stage, the use of illegal drugs can be associated with an increased risk of criminal activity caused by loss of awareness and disorders of the psychiatric condition. Including Indonesia, which showed an increasing trend in the BNN report in 2010-2015. In following up on these problems, researchers used a qualitative methodology using the Positive Youth Development (PYD) model and produced a tool called a Mine House. As a result, the formation of a Mine House as one of the real implementations of the development of the PYD model has proven to be able to improve the capabilities of young people including students of SMAN 21 Surabaya. Therefore, it can be concluded that the PYD logic model that has been applied in many developing countries is proven to be able to be applied in Indonesia, one of which is at SMAN 21 Surabaya with the Mine Houses tool as a medium for young communities to contribute positively.